1993
DOI: 10.1093/nar/21.9.2237
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated poly(A) loss and mRNA stabilization are independent effects of protein synthesis inhibition on α-tubulin mRNA inChlamydomonas

Abstract: In Chlamydomonas, the usual rapid degradation of tubulin mRNAs induced by flagellar amputation is prevented by inhibition of protein synthesis with cycloheximide. Evidence is presented that the ability of cycloheximide to stabilize alpha-tubulin mRNA depends on the time of addition. Addition of cycloheximide to cells before induction strongly stabilizes the induced mRNAs, while addition after their synthesis stabilizes them only transiently. Moreover, cycloheximide inhibition does not stabilize the same alpha-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

1993
1993
2004
2004

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 48 publications
3
10
0
Order By: Relevance
“…Figure 2B, D, and F shows mRNA levels in nondeflagellated cells treated with Act-D. Figure 2B and D shows that the constitutively expressed ␣1-tubulin mRNA and the tubHApG mRNA both disappear relatively slowly in the presence of Act-D. Although this experiment was not carried out long enough to obtain an accurate half-life, an approximate half-life of 70 to 75 min was calculated, consistent with previous determinations for ␣-tubulin mRNA (2,5). We know that Act-D was effectively inhibiting transcription in these studies, because rehybridization of the blots with a probe for a short-lived mRNA showed that it disappeared rapidly (data not shown).…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations
“…Figure 2B, D, and F shows mRNA levels in nondeflagellated cells treated with Act-D. Figure 2B and D shows that the constitutively expressed ␣1-tubulin mRNA and the tubHApG mRNA both disappear relatively slowly in the presence of Act-D. Although this experiment was not carried out long enough to obtain an accurate half-life, an approximate half-life of 70 to 75 min was calculated, consistent with previous determinations for ␣-tubulin mRNA (2,5). We know that Act-D was effectively inhibiting transcription in these studies, because rehybridization of the blots with a probe for a short-lived mRNA showed that it disappeared rapidly (data not shown).…”
Section: Resultssupporting
confidence: 85%
“…The blot is hybridized with an antisense HA probe that recognizes the fragment derived from the intact tubHApG mRNA but not the decay intermediate. This blot shows that the poly(A) lengths exhibited by the tubHApG mRNA are typical of those exhibited by the endogenous tubulin mRNAs (4,5). The induced tubulin mRNAs are synthesized in a transcriptional burst that peaks within 15 min and is essentially over by 30 min after deflagellation (2, 3).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In plant material not treated with CHX, results from the RNA gel blot/RT-PCR consistently concurred with the results obtained from the microarray analyses ( Figure 3). Some genes had enhanced expression in the presence of CHX compared with those not CHX treated ( Figure 3); this is consistent with prior observations of enhanced mRNA stability upon CHX treatment (Baker and Liggit, 1993;Goda et al, 2002). The relative stabilization of some transcripts upon CHX treatment indirectly suggests that posttranscriptional modifications may be occurring.…”
Section: Transcriptional Upregulation By Glucose Largely Requires De supporting
confidence: 89%